(untitled) (International Journal of Engineering and Computer Science, 2015)
Although tremendous progress has been made in the past years on video watermarking, there still exist a number of problems. We believe that the most important one is related to the compression rates, robustness against attacks and high security for privacy data. In digital image processing domain “achieving better compression rates in dual digital watermarking” is still area of concern. The proposed work shows the embedding of visible and invisible watermark during compression on the video encoder and the respective embedding approach on the video is termed as optimized compression/watermarking algorithm and system. The performance of the video watermarking is better when the complexity is low and this low complexity is achieved in our proposed work by discrete cosine transform (DCT). Finally, the results show the high correlation against different attacks in the extraction section. The proposed algorithm is more successful in order to overcome, the conventional algorithm drawbacks and more suitable to applied in the real time applications.